Analyzing the Relationship Between Anemia and Diabetic (Foot Ulcer) at Department of Medicine KTH Peshawar a Cross-Sectional Study - Usman Ali, Shahid Rizwan Safir, Bakhti Mahmood, Shah Umam, Abdul Quddos, Raza Muhammad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Diabetes complications like diabetic (foot ulcer) (DFU) are frequent and may be incapacitating. Patients with diabetes who have anemia have a higher chance of developing DFU. Objectives: To analyze the relationship between anemia and DFU in the patients. Methods: This study was carried out at the department of Medical Unit Khyber Teaching Hospital from 1st March 2022 to 31st March 2023 in Pakistan. Sample size 50 All patients with diabetes and DFU were included. The following demographic, clinical, and laboratory parameters were compared between patients with and without anemia ( age, sex, body mass index) (BMI), type of diabetes, duration of diabetes, glycosylated hemoglobin (HbA1c), and serum ferritin levels. Results: The study comprised 90 participants with both diabetes and DFU. 39 (43.3%) of these individuals had anemia. There was no significant difference in the [mean age] (p=0.664), [sex] (p=0.392),[ BMI] (p=0.532), type of diabetes (p=0.505), duration of diabetes (p=0.084), and HbA1c (p=0.194) between the [anemic and non-anemic] patients. However, the (mean serum ferritin levels) were significantly lower in anemic patients compared with non-anemic patients [p<0.001]. Conclusion: Lower serum ferritin levels are linked to anemia, a prevalent complication in DFU patients. To assess the involvement of anemia in the onset and course of DFU, further research is required. Keywords: Anemia, Diabetic, Foot Ulcer, Department of Medicine, KTH Peshawar, Cross-Sectional Study.